Penggunaan Permainan Edukatif Dalam Meningkatkan Motivasi Dan Prestasi Belajar IPA Di SMK - Sri Hemaliawati (International Forum of Researchers and Lecturers, 2023)
Science learning in vocational schools is important in the development of students' knowledge, but creative approaches are needed to improve motivation and achievement. This research explores educational games as a strategy. The aim is to understand the impact of educational games in improving students' science learning motivation and achievement. A qualitative approach was used in data collection. The results show the benefits of educational games: high engagement, motivation through elements of competition, rewards and fun, better understanding of science concepts, intensive practice, critical skills and sustained learning motivation. The implication of this research is that by integrating educational games into the science curriculum, educators can create an engaging and effective learning environment, help students develop a deeper understanding of science, and achieve better learning achievement. Thus, educational games are a valuable tool to advance science education in vocational schools.